Multitasking roles of mosquito labrum in oviposition and blood feeding - Choo, Young-Moo; Buss, Garrison K.; Tan, Kaiming; Leal, Walter S. (Frontiers in Physiology, 2015)
Reception of odorants by two main head appendages, antennae and maxillary palps, is essential for insects’ survival and reproduction. There is growing evidence in the literature suggesting that the proboscis is also an olfactory appendage and its function as an additional “antenna” has been previously proposed. We surmised that movements of the labrum towards blood vessel might be chemically oriented and, if so, there should be odorant receptors expressed in the labrum. To test this hypothesis, we first compared by quantitative PCR expression of odorant receptors (OR) from the Southern house mosquito, Culex quinquefasciatus in antennae and proboscis and, subsequently compared OR expression in various proboscis parts. Our data suggested that a receptor for the oviposition attractant, skatole, CquiOR21, was not expressed in proboscis, whereas a receptor for another oviposition attractant, 4EP (4-ethylphenol), CquiOR99, and a receptor for the insect repellent DEET, CquiOR136, were expressed in the stylet of the proboscis, particularly in the tip of the labrum. In a dual-choice olfactometer, mosquitoes having the stylet coated with nail polish were attracted to 4EP in the same manner as the untreated mosquitoes. By contrast, in an oviposition assay, the stylet-treated mosquitoes did not discriminate 4EP from control oviposition cups, whereas the untreated mosquitoes (as well as mosquitoes having the labella coated) laid significantly more egg rafts in cups treated with 4EP. Ablation experiments confirmed that 4EP was sensed by the labrum where CquiOR99 is highly expressed. Stylet-coated, labella-coated, and untreated mosquitoes laid significantly more egg rafts in skatole-treated cups than in control cups. Likewise, coating of proboscis structures with nail polish had no effect on DEET-mediated oviposition deterrence. In a behavioral arena designed to mimic a human arm, mosquitoes showed significantly reduced probing time when blood was impregnated with 4EP, i.e., they engaged more rapidly in continuous blood feeding as compared to untreated blood. The time of engagement for feeding in skatole-containing blood vs. untreated blood did not differ significantly. Taken together, these data suggest that 4EP reception by the labrum is important not only for oviposition decisions, but also for reducing probing and initiation of blood feeding.